Optimized nanospace of coordination isomers with selenium sites for acetylene separation. Issue 17 (4th August 2020) - Wang, Huijie; Behera, Nibedita; Wang, Suna; Dong, Qiubing; Wang, Zhaoxu; Zheng, Baishu; Wang, Daqi; Duan, Jingui
Abstract : Assisted by functional Cu and Se sites, a new group of porous isomers demonstrated systematically tunable C2 H2 /CO2 separation. Abstract : The safe storage and separation of acetylene (C2 H2 ) is difficult and essential, due to its explosive properties and wide usage for various industrial products. With a generally low energy cost, highly efficient adsorption separation has been considered as a promising solution. Taking advantage of the inbuilt nature of a tunable pore space, a porous coordination polymer (NTU-56 ) was prepared from a selenium-containing carboxylate ligand and Cu 2+ ions. Triggered by water at different temperatures, NTU-56 transformed into two other porous frameworks (NTU-57 and NTU-58 ) with different topologies and pore environments. Single-component gas adsorption experiments showed that this new group of porous isomers featured systematically varied adsorption selectivity for C2 H2 /CO2, two gases that have extremely similar molecular sizes and boiling points. More interestingly, among the isomers, NTU-58, a rare 2D, flexible, and water-stable framework, has the highest C2 H2 uptake (60 cm 3 g −1 ) and C2 H2 /CO2 selectivity (13.9, 1/1, v/v, 1 bar) at 273 K, derived from the synergetic effect of the unique pore sizes (4.5 and 5.5 Å) and pore surface polarity, where the Cu 2+ and selenium sites are exposed for preferred C2 H2 interactions. Efficient and recyclable C2 H2 /CO2 separation was also confirmed via breakthrough experiments, even with wet feed-gas.